Crude Oil Desalting Using Multi-Surfactant Based on a Best Dosage, Solvent and Mixing Ratio - Ali Hussein Khalaf; Mohammed Salah Rajab (Tikrit Journal of Engineering Sciences, 2019)
Crude oil desalting is the first processing step in a refinery. The objectives of crude desalting are the removal of salts, solids, and the formation of water from unrefined crude oil before the crude is introduced in the crude distillation unit of the refinery. The experimental work is divided into three schemes covering the effect of surfactant dosage, test different types of surfactants, and the effect of salt content on desalting efficiency. The results show that the crude oil desalting efficiency, increased with increasing surfactant quantity., The results indicate that desalting efficiency has lowered with increasing the salt content in crude oil. Also, the results show that the best solvent was toluene, and the best mixing ratio of solvent was 10 Vol. %.